The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5120/11666-7261
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Modified Booth Multiplier using Pipeline Technique on FPGA

Abstract: This paper presents 16×16 bit Radix-4 Modified Booth's Multiplier (MBM) optimized for high speed multiplication by using pipeline Technique. This paper aims at reduction of hardware utilization. This is accomplished by the use of 3:2 compressor adders. An efficient VHDL code has been written, successfully simulated on Modelsim 10.2 simulator and Xilinx 12.4 navigator is used for synthesizing the code. Simulation result shows the clock period of 2.689ns. The selected device to synthesize the code is xc3s500e-4p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The design achieved a reduction of delay by 8% for the parallel multiplier. N. Kaur and R.K. Patial [13] presented a fast 16x16 bit radix-4 modified booth multiplier using the pipeline technique. Authors have suggested the adder architecture by introducing the 3:2 compressor adders.…”
Section: A General Architecture Of Macmentioning
confidence: 99%
“…The design achieved a reduction of delay by 8% for the parallel multiplier. N. Kaur and R.K. Patial [13] presented a fast 16x16 bit radix-4 modified booth multiplier using the pipeline technique. Authors have suggested the adder architecture by introducing the 3:2 compressor adders.…”
Section: A General Architecture Of Macmentioning
confidence: 99%